Перша знахідка Laetisaria fuciformis (McAlpine) Burds. (Corticiaceae) в Україні - Акулов, О.Ю.; Джаган, В.В.; Сенчило, О.О.; Сухомлин, М.М. (Український ботанічний журнал, 2010)
Сообщается о находке нового для Украины вида Laetisaria fuciformis (McAlpine) Burds. (Corti ciaceae, Basidiomycota). Охарактеризованы его основные диагностические признаки. Data on finding of a fungus species new for Ukraine, Laetisaria fuciformis (McAlpine) Burds. (Corticiaceae, Basidiomycota), are provided. Main diagnostic characters of this fungus are characterized.